Research on the drug resistance mechanism of foodborne pathogens. (January 2022) - Ge, Hengwei; Wang, Yizhe; Zhao, Xihong
Abstract: Foodborne diseases caused by foodborne pathogens are one of the main problems threatening human health and safety. The emergence of multi-drug resistant strains due to the abuse of antibiotics has increased the difficulty of clinical treatment. Research on the drug resistance mechanism of foodborne pathogens has become an effective method to solve multi-drug resistant strains. In this paper, the four main drug resistance mechanisms, including reduced cell membrane permeability, efflux pump mechanism, target site mutation mechanism, and enzymatic hydrolysis, were used to systematically analyze the drug resistance of Salmonella, Listeria monocytogenes, and Escherichia coli . And the new methods were discussed that may be used to solve the drug resistance of foodborne pathogens such as CRISPR and bacteriophages. This review provided a certain theoretical basis for the treatment of foodborne diseases. Highlights: The four main drug resistance mechanisms were used to systematically analyze the drug resistance of foodborne pathogens. This review discussed the new methods that may be used to solve the drug resistance of foodborne pathogens.